The effect of electrolyte and additive concentration on zinc–nickel flow cell performance. (20th January 2021) - Trudgeon, David P.; Li, Xiaohong
Abstract: This work aims to identify a suitable electrolyte composition for the operation of a zinc–nickel flow cell at ambient temperature. The effect of varying electrolyte composition containing KOH, ZnO, tetraethylammonium hydroxide (TEAH) or tetrabutylammonium bromide (TEAB) electrolyte additives are investigated. A 15 mM concentration of TEAH is found to provide smooth and compact zinc depositions. Increasing concentrations of KOH are found to be detrimental to voltaic efficiency, with coulombic efficiency peaking in 6 M KOH. The coulombic efficiencies of both zinc and nickel electrodes improve with ZnO concentration. Galvanostatic zinc–nickel flow cell cycling yields the highest efficiencies in an electrolyte of 6 M KOH with 0.5 M ZnO and 15 mM TEAH, with coulombic, voltaic and energy efficiencies of 98%, 88% and 86%, respectively, over 70 stable charge/discharge cycles.